HUBUNGAN KELENGKAPAN DOKUMEN REKAM MEDIS DENGAN AKURASI CODING ICD -10 DI RUMAH SAKIT ISLAM MASYITOH BANGIL - Daniyah, Robiatud; Utami, Sri Erna; Ainul Khuluq, Moch (JRMIK, 2024)
One of the authorities of medical recorders is to carry out a system of clinical classification and codification of diseases and must refer to regulations that have been issued by WHO. The purpose of this study was to analyze the factors that affect the accuracy of coding outpatient medical record documents at RSI Masyitoh Bangil. The independent variable in this study is the completeness of medical record documents consisting of patient identity, history, diagnosis, physical examination, treatment and action, supporting examinations, service plans. The type of research used is quantitative research, using bivariate analysis. The results and conclusions obtained there is a clearly proven relationship between the accuracy of ICD 10 outpatient document codification with physical examination at p value = 0.302. And there is a relationship between the accuracy of ICD 10 codefication of outpatient documents with supporting examinations with results with p value = 0.002. And there is a real relationship between the accuracy of ICD 10 codefication of outpatient documents with treatment and action with a p value = 0.006. The results of statistical tests with a Sig (P-Value) value of <0.25 in bivariate chi square analysis can enter the multivariate analysis stage.